The Effect of Work Motivation and Discipline on Employee Performance Effectiveness - Althon Karaman Pongtuluran; Jens Batara Marewa (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Employee performance is a key factor in achieving company goals and is influenced by various aspects, including motivation and work discipline. Highly motivated employees tend to be more productive, while good work discipline creates a more structured and efficient work environment. This study aims to analyze the effect of work motivation and work discipline on the effectiveness of employee performance at PT. Mandala Finance, Makale Branch, Tana Toraja Regency. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to all employees of PT. Mandala Finance, Makale Branch. The sampling technique used was a saturated sampling method, and data analysis was conducted using Partial Least Square (PLS) with SmartPLS 3.2.9 software. The results show that work motivation positively affects employee performance effectiveness, where more motivated employees demonstrate optimal performance. Furthermore, work discipline also has a significant effect on performance effectiveness, as employees with high discipline levels adhere more to rules and work procedures. Therefore, the company is advised to enhance employee motivation and discipline to improve their performance effectiveness.